(-5)*(-5) is 25

if no ( ), then it becomes -5 * 5 is -25

if no ( ), then it becomes -5 * 5 is -25

(-5)*(-5) is 25

if no ( ), then it becomes -5 * 5 is -25

if no ( ), then it becomes -5 * 5 is -25

It would be a positive 25(+25) because a negative times a negative equals a positive(-x-=+)

It's positive 25 because:

- positive times positive is positive

- negative times negative is positive

- and, negative times positive is negative

- positive times positive is positive

- negative times negative is positive

- and, negative times positive is negative

I know a negative times a negative becomes a positive.. But if I remember right if one of the negatives are in () then it makes the answer a negative.. So I think the answer is -25

[^^^] = [ (-2) X (-3) ]

= [ (-2) X (-3) ] = [ - (-6) ] = [ { (-2) } X { (-3) } ] = [ - (-6) ] = [ { (+1) + (-3) } X { (+1) + (-4) } ] = [ - (-6) ] = [ { (+1) - (+3) } X { (+1) - (+4) } ] = [ - (-6) ] = [ { (+1) - (+3) } X (+1) - { (+1) - (+3) } X (+4) ] = [ - (-6) ] = [ { < (+1) X (+1) > - < (+3) X (+1) > } - { < (+1) X (+4) > - < (+3) X (+4) > } ] = [ - (-6) ] = [ { < + [ (+1) X 1 ] > - < + [ (+3) X 1 ] > } - { < + [ (+1) X 4 ] > - < + [ (+3) X 4 ] > } ] = [ - (-6) ] = [ { < [ (+1) X 1 ] > - < [ (+3) X 1 ] > } - { < [ (+1) X 4 ] > - < [ (+3) X 4 ] > } ] = [ - (-6) ] = [ { < (+1) X 1 > - < (+3) X 1 > } - { < (+1) X 4 > - < (+3) X 4 > } ] = [ - (-6) ] = [ { < (+1) > - < (+3) > } - { < (+4) > - < (+12) > } ] = [ - (-6) ] = [ { (+1) - (+3) } - { (+4) - (+12) } ] = [ - (-6) ] = [ { (+1) - (+3) } - { (+4) + (-12) } ] = [ - (-6) ] = [ (+1) - (+3) - (+4) - (-12) ] = [ - (-6) ] = [ (+1) - (+3) - (+4) + (+12) ] = [ - (-6) ] = [ (+1) + (+12) - (+3) - (+4) ] = [ - (-6) ] = [ { (+1) + (+12) } - { (+3) + (+4) } ] = [ - (-6) ] = [ { (+13) } - { (+7) } ] = [ - (-6) ] = [ (+13) - (+7) ] = [ - (-6) ] = [ (+6) ] = [ - (-6) ] = [ + (+6) ] = [ - (-6) ] = [ - (-6) ] = [ - (-6) ] = [ + (+6) ] = [ + (+6) ] = [ (+6) ] = [ (+6) ] = [ (6) ] = [ (6) ] = [ 6 ] = [ 6 ]

= [ (-2) X (-3) ] = [ - (-6) ] = [ { (-2) } X { (-3) } ] = [ - (-6) ] = [ { (+1) + (-3) } X { (+1) + (-4) } ] = [ - (-6) ] = [ { (+1) - (+3) } X { (+1) - (+4) } ] = [ - (-6) ] = [ { (+1) - (+3) } X (+1) - { (+1) - (+3) } X (+4) ] = [ - (-6) ] = [ { < (+1) X (+1) > - < (+3) X (+1) > } - { < (+1) X (+4) > - < (+3) X (+4) > } ] = [ - (-6) ] = [ { < + [ (+1) X 1 ] > - < + [ (+3) X 1 ] > } - { < + [ (+1) X 4 ] > - < + [ (+3) X 4 ] > } ] = [ - (-6) ] = [ { < [ (+1) X 1 ] > - < [ (+3) X 1 ] > } - { < [ (+1) X 4 ] > - < [ (+3) X 4 ] > } ] = [ - (-6) ] = [ { < (+1) X 1 > - < (+3) X 1 > } - { < (+1) X 4 > - < (+3) X 4 > } ] = [ - (-6) ] = [ { < (+1) > - < (+3) > } - { < (+4) > - < (+12) > } ] = [ - (-6) ] = [ { (+1) - (+3) } - { (+4) - (+12) } ] = [ - (-6) ] = [ { (+1) - (+3) } - { (+4) + (-12) } ] = [ - (-6) ] = [ (+1) - (+3) - (+4) - (-12) ] = [ - (-6) ] = [ (+1) - (+3) - (+4) + (+12) ] = [ - (-6) ] = [ (+1) + (+12) - (+3) - (+4) ] = [ - (-6) ] = [ { (+1) + (+12) } - { (+3) + (+4) } ] = [ - (-6) ] = [ { (+13) } - { (+7) } ] = [ - (-6) ] = [ (+13) - (+7) ] = [ - (-6) ] = [ (+6) ] = [ - (-6) ] = [ + (+6) ] = [ - (-6) ] = [ - (-6) ] = [ - (-6) ] = [ + (+6) ] = [ + (+6) ] = [ (+6) ] = [ (+6) ] = [ (6) ] = [ (6) ] = [ 6 ] = [ 6 ]

It is a positive 25.

Its positive but you need the parentheses

I believe you are right, I know that if you take a negative times a negative it becomes a positive. However if I remember right if one of the negatives is in () it does make the answer negative.

Didn't find the answer you were looking for?